Diatoms in Paleoenvironmental Studies of Peatlands - Rafael Carballeira; Xabier Pontevedra-Pombal (Quaternary, 2020)
The great diversity of diatoms in aquatic ecosystems and their close relationship with water chemistry make them one of the most informative and widely used biological proxies in paleoenvironmental studies of wetlands, except for peatland ecosystems. Currently, significant controversy still exists over the preservation of diatoms in peat. However, considerable evidence indicates that diatoms remain in good condition in minerotrophic peatlands, and they have been successfully used in paleoenvironmental studies in high-latitude regions and especially in Southern Europe.